Plantas medicinais associadas a desordens mentais e neurológicas: uma comparação entre etnofarmacologia e testes farmacológicos - Costa, Giovanna Felipe Cavalcante e (2018)
The use of plants for therapeutic purposes has been reported in South America since ancient times and occurs in many communities as the only form of treatment of diseases. The use of medicinal plants ranges from respiratory, gastrointestinal problems to diseases of the Neural System. Indications such as demulcent, sedative and even for dementias are frequent. Despite the use in various social classes some problems are related to use of medicinal plants like contamination by other plants or parts of insects, decreased expected effects, and adverse effects are common. In addition to these barriers to commercialization and inspection, there is a demand for the training of health professionals. Primary health care professionals can act to guide the use of medicinal plants and contribute to the reduction of adverse effects due to inadequate dose or indication. The objective of this study was to carry out a bibliographic survey of the plants used for the Neural System Disorders and to compare these results with pharmacological tests. In the literature there are pharmacological tests that prove the medicinal actions of these plants. However, when compared to the popular indications, there may be differences. Thus, more ethnobotanical studies and confrontation with pharmacological tests are necessary, besides including information pertinent to this therapy in the training of health care professionals.